COHESION IN SELECTED EDITORIALS FROM TWO NIGERIAN NEWSPAPERS (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2023)
This study analyses the editorials of Vanguard and Guardian Nigerian newspapers to investigate how cohesive devices are used in textual creation and meaning realization in these texts. Four editorials were purposefully selected from the period of April to December 2021. This period is pivotal in understanding the escalated level of insecurity in Nigeria. It marked a basic departure from earlier attacks that targeted worship centers and marketplaces. Within this period, too, two serving States Governors narrowly escaped the bullets of the terrorists, namely: Governors Samuel Ortom of Benue State, and Babagana Zullum of Borno State. Halliday and Hasan's (1976) model of cohesion was adopted as the theoretical framework.  A qualitative method was used for the data analysis. The framework is to enable the researcher to find out the effect of lexical choices as cohesive devices in the creation of semantic realization of the editorial text. The findings show that cohesive devices like reference, substitution, and ellipsis were used as grammatical items to refer to lexical elements that precede them. The devices help the writers to achieve their aim of making their readers see the connectivity of lexical words in meaning realization. The lexical cohesion, on the other hand, were used by the writers to relate to other lexical items that occurred previously in the texts. The editorial writers used the lexical cohesion to create texture in the text, and to also express their opinions towards the insecurity situation in Nigeria. The study therefore, recommends more studies of this nature in other newspapers and media platforms to see how their choices of lexical cohesion enact social realities.
Keywords: Cohesion,Nigeria,NewspaperEditorials,LexicalChoices,CohesiveDevices